The male reproductive biology of cultured river catfish, Mystus nemurus (Cuvier & Valenciennes) - Christianus, Annie (2001)
Mystus nemurus broodstock bought from Rawang, Selangor in March 1995, conditioned in the Hatchery Unit of Universiti Putra Malaysia were used for all the experiments including larvae production. In the first experiment, morphologically the testis has shown to consist of a mass of finger like structures with an anterior part accommodating clusters of spermatogenic cells and spermatozoa; and the posterior part, displaying some muscle layers and ducts, described as spermatogenic and the glandular testis, respectively. Electron microscopy showed that the morphology of the M nemurus spermatozoa consist of a head measuring 1.88 ± 0.01 µm in diameter; midpiece, 1.69 ± 0.02 µm in width and flagellum, 11.42 ± 0.07 µm in length. In the second experiment, males M nemurus were distinguishable only at 5-monthold and gonads started differentiating at 8-month-old. Histometric measurement of the lumen areas of 11, 12 and 13-month-old showed a significant increase (P < 0.05) in sizes compared to 8, 9 and 10-month-old and a significant (P < 0.05) correlation with r = -0.567 between these lumen and spermatogenic areas from the initial stage of differentiation. Males were found to produce spermatozoa at 13-month-old but only attained the ability to fertilize eggs at 17 -month-old. In the third experiment, among the various physical and biochemical characteristics determined between non-treated and carp pituitary extract (CPE) treated groups, significant differences (P < 0.05) were detected in the milt volume, pH, osmolality, glucose, urea, total protein, sperm density and total sperm count. The significantly (P < 0.05) higher fertilization rate of CPE treated group showed that hormone treatment on M nemurus produces better quality of milt and spermatozoa. In the last experiment, the testosterone (T) and l1-ketotestosterone (ll-KT) levels in the circulating plasma of matured and immature males M nemurus measured by radioimmunoassay (RIA) and enzyme linked immunosorbent assay (ELISA), ranged from 0.25 to 2.34 and 0.75 to 4.58 nglml; and 0.19 to 1.57 and 0.49 to 4.19 ng/ml, respectively, with ll-KT as the dominating androgen. In the one-year duration, T and l1-KT profiles of the two groups of matured and immature showed a significant correlation (P < 0.05) with r = 0.814 and 0.682, respectively. Hormones profiles suggested the association of these T and 11-KT with the reproductive cycle and gonadal development of the matured and immature groups, respectively.